2018
DOI: 10.1159/000495675
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Circular RNA circ_0005230 Indicates Dismal Prognosis in Breast Cancer and Regulates Cell Proliferation and Invasion via miR-618/ CBX8 Signal Pathway

Abstract: Background/Aims: Circular RNAs (circRNAs) are a class of non-coding RNAs. They have been proved to be critically involved in tumorigenesis and progression of malignancies through competing endogenous RNA (ceRNA) mechanism. Nevertheless, the exploration between circRNAs and pathogenesis of breast cancer (BC) is limited. Previously, circ_0005230 was identified upregulated in BC tissues screened by circRNA microarray. In the present study, we aimed to investigate the expression pattern, functional role, and mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 26 publications
2
44
0
2
Order By: Relevance
“…For example, circPVT1 contributes to non-small cell lung cancer (NSCLC) cell growth and migration by inhibiting miR-125b to activate E2F2 expression [13]. Circ_0005230 is overexpressed in breast cancer and promotes tumor cell division and invasiveness through miR-618/CBX8 signaling [14]. CircMMP9 is upregulated by EIF4A3 in glioblastoma and contributes to tumor development by sponging miR-124 [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, circPVT1 contributes to non-small cell lung cancer (NSCLC) cell growth and migration by inhibiting miR-125b to activate E2F2 expression [13]. Circ_0005230 is overexpressed in breast cancer and promotes tumor cell division and invasiveness through miR-618/CBX8 signaling [14]. CircMMP9 is upregulated by EIF4A3 in glioblastoma and contributes to tumor development by sponging miR-124 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we identified circ_0005230 was elevated in breast cancer tissue samples and was linked to breast cancer patients’ unfavorable prognosis. Furthermore, the biological functions of circ_0005230 was partially attributed to its modulation on miR-618/CBX8 signaling [14]. Circ_0005230 is located at chr1:172109619-172113577 and is spliced from DNM3OS (DNM3 opposite strand/antisense RNA) gene (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…7 In this study, we found that upregulation of circ-CDC45 is related to larger tumor size and higher WHO grades. 8,9 For example, circ-NT5E served as a sponge against miR-422a to facilitate GM oncogenesis. In addition, we found that GM patients with elevated circ-CDC45 level displayed a shorter survival time than the patients with low expression, suggesting that circ-CDC45 may be a potential prognostic biomarker of GM.…”
Section: Discussionmentioning
confidence: 99%
“…5 The rapid development of RNA genomics has highlighted the oncogenic or anti-oncogenic role of circRNAs in many cancers, especially in GM. 8 For GM, circ_0034642 could facilitate tumorigenesis via the miR-1205/BATF3 axis, as reported by Yang et al 9 MicroRNAs (miRNAs) regulate downstream target expression at posttranscriptional level. 7 circ_0005230 functions as an efficient miR-518 sponge, thereby releasing the expression inhibition of CBX8 in breast cancer.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation